Hungry Bengal : War, Famine and the End of Empire - Janam Mukherjee (India HarperCollins Publishers India, 2015)
Representing both a major front in the Indian struggle against colonial rule, as well as a crucial front in the British/American conflict with Japan during World War II, Bengal stood at the crossroads of complex forces that describe an era of political uncertainty, social turmoil, and collective violence. The period (1939-1946) can be defined, above all, by three interrelated events: World War II, the Bengal famine of 1943, and the Calcutta riots of 1946. Mobilization for war began in 1939, but Britain's sense of urgency was difficult to impress upon a skeptical Indian population already chaffing under the injustices of colonial rule and grave economic hardship. This book examines this topic.
Include Maps, Notes, Bibliography and Index.
War, Famine and the End of Empire.
Keywords: World War (1939-1945) -- India--Bengal -- Social aspects -- Famines